Traces of social mobilization against last Argentinean dictatorship in the social struggles of the late nineties in La Matanza (1986-2001) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this article we analyze the traces of the social struggles against the Military Civic Dictatorship (1976-1983) in the constitution and mobilization of the “Red de Barrios de La Matanza” in late 1990s and early 2000s. The main output is that the collective narra- tions about these processes are presented as continuity with antecedent experiences, such as the land squatting, and contemporary experiences, such as the pickets of former oil workers in Patagonia and the North of the country. This process, permits to these so- cial actors, normally excluded of union representation and government interlocution, to express themselves as part of labor class. The corpus in this article consists of documents, in-depth interviews, chronicles in national newspapers and field records collec- ted in the period 1999-2008.
Keywords: traces, memory, pickets, La Matanza